The Dimensions of the Learning Organization Questionnaire (the DLOQ): A Nontechnical Manual. (May 2013) - Watkins, Karen E.; O'Neil, Judy
The Problem: No readily accessible source of information is available to answer questions posed by those who seek to use the DLOQ about its construction, utility, and reliability. The Solution: This article traces the development of theoretical constructs that undergird the survey, outlines the steps of survey construction, and responds to frequently asked questions. The Stakeholders: Human resource and organization development (HROD) scholars who would use the DLOQ in studies of organizational culture need accurate information about the instrument. HROD practitioners who plan to use the instrument also need information about its utility and reliability to share with stakeholders and to ensure that high quality data will inform their interventions.